Peranan Satuan Polisi Pamong Praja dalam Menjaga Ketertiban Dan Ketentraman Serta Pelayanan Masyarakat di Kota Makassar - Nurlina Subair; Muhajir Muhajir (JED (Jurnal Etika Demokrasi), 2017)
This study aims to describe how the role of civil service police unit in maintaining order and peace and public service in Makassar City in accordance with the main tasks and functions and the factors that influence the role of government in maintaining order and peace in Makassar. The type of research used in this study is descriptive with the basic case study research. Technique of collecting data using observation and interview. The result of the research shows that the coordination role of Satuan Pamong Praja Police Unit in community service is not separated from how the form of its supervision to the Local Regulation which is run in accordance with the Main Task and its Function as the enforcer of the local regulation. The factors that become consideration in the service to the community and ketentraman and keteriban in Makassar in this case the enforcement of Regional Regulation No. 9 of 2002 is the level of education, facilities and equipment associated with the tool that will support the implementation of its duties in enforcing the Regional Regulations in Makassar City, and the Role of Government as a regulator and also a policy maker that will support the implementation of the tasks of Satuan Pamong Praja Police Unit in the enforcement of Regional Regulations in Makassar CityKeywords: The Role of Coordination in Community Service